Aspekty prawne bezpieczeństwa publicznego - Kiczka, Karol (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Ensuring public safety is a public task regulated in domestic and international legal systems. Polish Constitution allocates this task to executive authorities: the President of the Republic of Poland and the Council of Ministers. In order to accomplish the task these constitutional organs of the Polish state are legally obligated to effectively cooperate, and according to the Crisis Management Act 2007, it is the governmental administration that should play the essential role in the field of public safety.
Keywords: legal aspects; public safety